Where are we now? A review of research on the history of women's soccer in Ireland. Issue 2 (3rd April 2019) - Byrne, Helena
ABSTRACT: It is a common fact that women's sport and leisure history, especially in male dominated spheres, and more specifically football, have been ignored by many academics. However, in recent years there have been major developments in digital technology that have changed the nature of the type of research that can be done. Access to tools to facilitate field research are relatively cheap and with the high volume of digitisation projects that have taken place over the last few years as well as the increasing number of born digital resources that have been published, there are new opportunities. In relation to women's soccer in Ireland, this paper asks the question – where are we now? The argument will review the current literature on this subject and outline potential approaches for future research.